Urgências hospitalares: aplicação de data mining na classificação das falsas urgências – estudo de caso - Magalhães, Filipe Ricardo Oliveira (2020)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence